Empowering Community: The Role of Health Education and Acupressure Socialization in Independent Pain Management in Desa Lepasan - Eko Yulianto; Milasari Milasari; Hanifa amini; Gati Handayani; Isti Qamah; Nurrani Fitriani (UrbanGreen Central Media, 2026)
Pain impacts quality of life, requiring safe, non-pharmacological alternatives like acupressure. This community empowerment initiative in Desa Lepasan enhanced public knowledge and skills for independent pain management. Health education and hands-on demonstrations were conducted with 32 participants. Pre- and post-tests evaluated their understanding and pain levels. The program significantly improved public understanding, transforming participants into individuals capable of identifying meridian points independently. This enhanced knowledge triggered positive clinical outcomes, where 90.6% of participants (29 respondents) reported distinct pain relief, and the average pain scale dropped by 55.8%, from 4.03 (moderate pain) to 1.78 (mild pain). Structured health education successfully builds community understanding and practical independence, making self-acupressure an effective, safe, and sustainable strategy for localized pain management.